(untitled) (Research, Society and Development, 2020)
This manuscript aimed to present the conceptions of practice identified from an investigation on the initial training of teachers in three degrees in chemistry in academic units of the federal education, professional and technological network in Pernambuco, Brazil. The pedagogical projects of the three courses were analyzed in which the conception of practice was particularly observed from the curricular components "practice as a curricular component" and "supervised internship". The qualitative research of the documentary analysis type had the data analyzed based on the technique of content analysis (Bardin, 2011; Moraes, 1999). The data were categorized thematically and the analysis was anchored both in the theoretical framework and in the legal devices that guide the training and teachers in Brazil. As results, it can be affirmed that the PPC investigated have an innovative curriculum, however hybrid, because it maintains the traditional form of disciplinary organization, which has been configured as a contradiction, which, however, is considered acceptable in the movement and moment of curricular changes. PPC meets legal requirements, as well as the workload of both PCC and ES, but the practices are not clear enough, or a more detailed description of them almost always cannot be verified. Moreover, the conceptions of practice are almost always diffuse, it does not have its theoretical foundations clearly declared.